Harry Potter and the order of phoenix - Rowling,J.K (United state of America: Scholastic Press, 2003)
Harry Potter and the Order of the Phoenix is the fifth book in J.K. Rowling's Harry Potter series. In this installment, Harry returns to Hogwarts for his fifth year, facing increasing danger from the dark wizard Voldemort, who is rising to power. The Ministry of Magic refuses to acknowledge Voldemort's return, leading to widespread disbelief about his threat. At school, Harry and his friends, Ron and Hermione, discover that many students are unaware of the true danger. In response, Harry secretly forms a group called "Dumbledore's Army" (DA) to teach his peers defensive magic. Meanwhile, Harry is troubled by disturbing dreams that seem to be linked to Voldemort$1 (Bs plans. As the story unfolds, Harry learns about the prophecy that connects him to Voldemort, which suggests that one must ultimately defeat the other. He also faces struggles within the school, including conflict with the Ministry-appointed professor, Dolores Umbridge, who becomes increasingly tyrannical in her rule over the school. The climax of the story takes place at the Ministry of Magic, where Harry and his friends go to rescue his godfather, Sirius Black, who is captured by Death Eaters. A battle ensues, and tragically, Sirius is killed by Bellatrix Lestrange. Harry is left devastated by the loss. The book concludes with Harry more determined than ever to stop Voldemort, but now fully aware of the deep connection between them and the challenges that lie ahead. The events of this book mark a turning point in Harry$1 (Bs journey, as he prepares for the coming battles.s
Harry Potter and the Order of the Phoenix is a pivotal entry in J.K. Rowling's beloved fantasy series. This book delves deeper into the darker themes of the wizarding world as Harry faces not only the external threat of Voldemort's return but also the internal struggles of growing up, dealing with loss, and grappling with authority. The narrative explores the complexities of Harry$1 (Bs character, showing him at his most vulnerable and defiant. The tension between Harry and the Ministry of Magic highlights the political corruption and denial of truth, while his formation of Dumbledore's Army illustrates his leadership qualities and desire to protect his friends and the magical community. The introduction of new characters, such as the oppressive Dolores Umbridge, who becomes the embodiment of authoritarianism at Hogwarts, creates an environment of resistance, mirroring the larger conflict between good and evil. The emotional climax with Sirius Black's death marks a significant turning point in Harry$1 (Bs journey, deepening his resolve against Voldemort. Themes of friendship, loyalty, identity, and the consequences of power are central to the story. The book also foreshadows the darker, more dangerous battles ahead, setting the stage for the final confrontations in the series. The Order of the Phoenix stands as a critical moment in the overall arc, demonstrating the personal growth of the characters and the increased stakes of the war against dark forces.s